Identification of necroptosis-related genes in Parkinson’s disease by integrated bioinformatics analysis and experimental validation - Lei, Cheng; Zhongyan, Zhou; Wenting, Shi; Jing, Zhang; Liyun, Qin; Hongyi, Hu; Juntao, Yan; Qing, Ye (Frontiers in Neuroscience, 2023)
Purpose: Screen necroptosis-related genes related to Parkinson's disease with bioinformatics analysis by searching the GEO Database. Method: Download the Parkinson's disease-related datasets GSE762 and GSE20141 from the GEO Database, obtain the genes related to Parkinson's disease based on necroptosis by gap analysis, cluster analysis, enrichment analysis and WGCNA analysis, and analyze biological relationships of related genes by using PPI network construction, key gene-miRNA network construction, transcription factor-target gene network construction and immune infiltration interaction analysis. Result: 12 necroptosis-related genes ASGR2, CCNA1, FGF10, FGF19, HJURP, NTF3, OIP5, RRM2, SLC22A1, SLC28A3, WNT1, WNT10B were obtained by screening, among which ASGR2, FGF10, FGF19, HJURP, NTF3, RRM2, SLC22A1, SLC28A3 and WNT1 genes were significantly increased in expression in Parkinson’s patients, while CCNA1, OIP5, WNT10B genes were significantly decreased in them. With blood samples from clinical Parkinson’s patients validated by using RT-PCR, OIP5 was consistent with the predicted results. Conclusion: OIP5 is screened as a potentially relevant gene for the treatment of PD by using bioinformatics analysis, which provides a reference for Parkinson's disease research.